Cabozantinib Cutaneous Toxicity—Comprehensive Review - Cristina Violeta Tutunaru; Dragos Ovidiu Alexandru; Sanda Amelia Dracea; Loredana Ungureanu; Liliana Gabriela Popa; Cristina Beiu (Life)
Background: In the context of modern cancer therapy, the management of adverse effects of systemic therapies can lead to the avoidance of underdosing and withdrawal and increases in the quality of the therapeutic act and the quality of life. This review offers an overview of the skin-related toxicities associated with Cabozantinib, a multikinase inhibitor (MKI) that is approved for treating advanced kidney cancer, hepatocellular carcinoma, and medullary thyroid cancer. It covers the most common dermatological side effects, such as palmar–plantar erythrodysesthesia, stomatitis, hair alterations, xerosis, scrotal erythema, and subungual splinter hemorrhages. Additionally, this review includes suggested preventive strategies and management approaches based on the severity of these adverse effects.